Coaching Clinic Peningkatan Profesional Guru melalui Karya Ilmiah bagi Guru Sekolah Dasar - Syunu Trihantoyo; Shelly Andari; Mohamad Syahidul Haq (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
The era of the Education Revolution 4.0 has now been felt and become a part of the education process and has an impact on the action of realizing teacher professionalism. About educational issues, as stated above, the purpose of implementing this article is to provide knowledge and skills for teachers in making classroom action research reports so that they can increase their professionalism. The method of this training activity is carried out by lectures, discussions, questions, and answers, and mentoring. This activity was attended by 24 participants from elementary school teachers throughout the city of Surabaya who had filled out the online registration (google form). The result of this training was that teachers knowledge and skills increased and could lead to the realization of professional teachers. This can be seen from the results of the training evaluation data analysis, which overall participants rated this activity in the outstanding category with a score range of 55-64. The training materials that the participants have mastered are good practice in classroom learning, the nature of classroom action research reports, writing classroom action research reports, and disseminating classroom action research reports. Mentoring is done by reviewing class action research reports from participants and providing feedback for improvements. Dissemination by submitting relevant educational journals and classroom action research journals for the trainees.